Urgensi Lingustik Dalam Memahami Model Dakwah Dalam Al-Qur’an - Abdul Kosim (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2023)
The Qur'an as a guide for Muslims covers various aspects of life, including aspects of proselytizing. The purpose of this study is to determine the linguistic urgency in understanding the model of proselytizing in the Qur'an. This research uses a descriptive method with a content analysis model, while the source of the data is the lexical and contextual meaning of the words al-hikmah, al-mauidzhah and al-mujaadalah from the dictionary of Mu'jam al-lughah al-Arabiyah al-mu'ashiroh by Ahmad Mukhtar Umar, Mu'jam alfadz al-Qur'an al-Karim by Raghib al-Ashfahani and al-wujuuh wa an-nadzhair by Abu Hilal al-Askary. The conclusion of this study is that Lingustics through one of its branches, namely Semantics, has urgency in understanding the verses of the proselytizing model. Among them is an understanding of the textual meaning and contextual meaning of the words hikmah, mauidzah hasanah and mujaadalah in the Qur'an.